До характеристики сутності та змісту державного регулювання в агропромисловій сфері - Дегтярьова, С. В.; Dehtiarova, S. V. (Юридичний бюлетень. - 2019. - Вип. 11, ч. 1. - С. 160-166, 2019)
Визначено сутність та зміст державного регулювання в агропромисловій сфері. З’ясовано, що під державним регулюванням можна розуміти цілеспрямований вплив органів державної влади на суб’єктів агропромислового комплексу через застосування у сукупності економіко - та адміністративно-правових заходів, розроблення, схвалення, упровадження політико-правових рішень, спрямованих на забезпечення координації та контролю суб’єктів правових відносин, установлення ринкових відносин та розвиток агропромислового комплексу, поліпшення організації виробництва і доведення до споживача продукції сільського господарства тощо. Наголошено, що сутність державного регулювання полягає у: застосуванні державою правових, адміністративних та економічних важелів щодо регулювання поведінки учасників аграрних правовідносин; прийнятті нормативно-правових актів; створенні, організації діяльності та визначенні компетенції системи державних органів у галузі сільського господарства та ін.

In the article, on the basisof analysis of norms of the current legislation of Ukraine and scientific views of scientists, the essence and content of state regulation in the agro-industrial sphere are determined. It is established that the subjects of state regulation of the agro-industrial complex are generally bodies of executive power, which besides state-legal regulation of agriculture, ensure compliance with agrarian legislation, management of subordinate structures, as well as bodies of agricultural inspections and control over the activity of agricultural producers. It has been found out that state regulation can be understood as the purposeful influence of the state authorities on the subjects of the agro-industrial complex, through the application of a set of economic and administrative-legal measures, development, approval, implementation of political and legal decisions aimed at ensuring coordination and control subjects of legal relations, establishment of market relations and development of agro-industrial complex, improvement of organization of production and bringing to the consumer of agricultural products and more. It is concluded that the essence of state regulation is: the application of legal, administrative and economic levers by the state to regulate the behavior of participants in agrarian legal relations; adoption of normative legal acts, creation, organization of activity and determination of competence of the system of state bodies in the field of agriculture, etc. And in modern conditions, only the state can: ensure the most rational use of agricultural land, equality of all forms of ownership and management, guarantee the development of entrepreneurship, production of necessary and quality products; apply such economic levers as tax privileges, subsidies, subsidies, preferential lending, state purchases of agricultural products to ensure the state's food security and fulfillment of social functions, state funding of research in priority agrarian industries.

Определены сущность и содержание государственного регулирования в агропромышленной сфере. Отмечено, что сущность государственного регулирования заключается в: применении государством правовых, административных и экономических рычагов по регулированию поведения участников аграрных правоотношений; принятии нормативно- правовых актов; создании, организации деятельности и определении компетенции системы государственных органов в области сельского хозяйства и т. д.
On the characteristics of essence and content of public administration in agro-industrial sphere
Keywords: державне регулювання; агропромислова сфера; правове регулювання; нормативно-правовий акт; state regulation; agro-industrial sphere; legal regulation; normative-legal act; государственное регулирование; агропромышленная сфера; правовое регулирование; нормативно- правовой акт